Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Ukraina - Yunus, Nur Rohim (UIN Jakarta, 2021)
The Ukrainian government is a presidential system, and the country is a unitary, democratic republic. Unitary states are characterized by the concentration of political and administrative power within the central government, which is located in Kiev. The president is the head of state and the head of government. He is elected by the people directly, which makes him the head of government as well as the head of state. In addition, the Prime Minister of Ukraine is the individual who is accountable for the day-to-day implementation of the policies that are implemented by the government. Ukraine's political structure displays a combination of aspects of presidential and parliamentary systems of government, with the prime minister lending a parliamentary feel to a traditionally presidential framework.